Strength and Pore Structure Development of High-Plasticity Clay Treated with MK-Blended Cement - Qian Guo; Mingli Wei; Haochen Xue; Changhui Gao; Guangyin Du (Advances in Civil Engineering)
This paper focuses on the strength development and pore structure evolution of high-plasticity clay mixtures treated with metakaolin- (MK-) blended ordinary Portland cement (OPC). The unconfined compressive strength (fcu) of treated soil mixtures is measured to study the effect of MK replacement. The microstructural study is carried out by mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The results showed that the MK replacement led to the decrease of unconfined compressive strength of OPC-treated soil mixture cured for 28 days, but the influence on 7 days strength was negligible. However, the MK addition also enhanced the unconfined compressive strength significantly. The MK addition provided more cementitious products by secondary hydration and pozzolanic reaction, which would give rise to a notable filling effect by turning the large pores (1 to 10 μm) into smaller ones (0.1 to 1 μm). However, the MK replacement led to a decrease of cementitious products due to the lack of calcium hydroxide (CH) in soil mixture, and thus the effect on pore structure refinement was reduced. Nevertheless, the presence of MK enhanced the unconfined compressive strength cured for 7 days, due to the high reactivity of MK with CH.